(untitled) (Research, Society and Development, 2021)
Objective: Assess the most frequent forms of infringement of the Brazilian Norm for the Marketing of Food for Infants and Early Childhood Children, nipples, pacifiers, baby bottles and nipple protectors - NBCAL, regarding the sale of infant formulas whose commercial promotion is prohibited. Methods: A cross-sectional study was carried out in 2018 in pharmacies and supermarkets in the cities of Belém and São Paulo, which marketed the products covered by NBCAL, the interviewers were trained on the NBCAL and used a structured electronic form to record the infringements found. in these places. Data description was made by absolute and relative frequency and 95%CI. Results: 200 establishments in Belém and 199 in São Paulo were evaluated, of which 11% presented infractions in the city of Belém and 9.5% breached the Standard in São Paulo. The most frequent infractions were: price promotion in Belém (52%) and São Paulo (46.2%), and special exhibition in Belém (10%) and São Paulo (35.9%), it was also possible to verify the simultaneous occurrence of the two offenses in Belém (38%) and São Paulo (17.9%). Conclusions: Although 32 years have passed since the institution of NBCAL, there are still recurrent infringements of the legislation in products whose commercial promotion is prohibited, this study reinforces the need for greater inspection in commercial establishments and companies that sell products that are NBCAL objects.